2015
DOI: 10.3892/ijmm.2015.2366
|View full text |Cite|
|
Sign up to set email alerts
|

Sevoflurane post-conditioning reduces rat myocardial ischemia reperfusion injury through an increase in NOS and a decrease in phopshorylated NHE1 levels

Abstract: The protective effects of sevoflurane post-conditioning against myocardial ischemia/reperfusion (I/R) injury (MIRI) have been previously reported. However, the mechanisms responsible for these protective effects remain elusive. In this study, in order to investigate the molecular mechanisms responsible for the protective effects of sevoflurane post-conditioning on isolated rat hearts subjected to MIRI, Sprague-Dawley rat hearts were randomly divided into the following 6 groups: i) the sham-operated control; ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 41 publications
4
35
0
Order By: Relevance
“…Previous studies showed that sevoflurane could completely prevent the neuronal eosinophilic damage of the brain in incomplete cerebral ischemia and improve neurological outcomes after severe cerebral ischemia in rats compared with animals anesthetized with Zoletil [29,30]. A previous study conducted by Cao et al demonstrated that sevoflurane post-conditioning could significantly attenuate myocardial I/R injury and inhibit cardiac cell apoptosis and excessive autophagy [31]. However, compared with the Sevo + I/R group, the LVEF and LVFS of the si-LINC00652 + Sevo + I/R group increased, whereas the LVEF and LVFS of the mice in the H89 + Sevo + I/R group decreased and returned to the level of the I/R group compared with the Sevo + I/R group, suggesting that interfering with the expression of LINC00652 could alleviate the degree of myocardial I/R injury, while inhibiting the cAMP/PKA signaling pathway could strengthen the degree of myocardial I/R injury in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that sevoflurane could completely prevent the neuronal eosinophilic damage of the brain in incomplete cerebral ischemia and improve neurological outcomes after severe cerebral ischemia in rats compared with animals anesthetized with Zoletil [29,30]. A previous study conducted by Cao et al demonstrated that sevoflurane post-conditioning could significantly attenuate myocardial I/R injury and inhibit cardiac cell apoptosis and excessive autophagy [31]. However, compared with the Sevo + I/R group, the LVEF and LVFS of the si-LINC00652 + Sevo + I/R group increased, whereas the LVEF and LVFS of the mice in the H89 + Sevo + I/R group decreased and returned to the level of the I/R group compared with the Sevo + I/R group, suggesting that interfering with the expression of LINC00652 could alleviate the degree of myocardial I/R injury, while inhibiting the cAMP/PKA signaling pathway could strengthen the degree of myocardial I/R injury in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Sevoflurane, a commonly used inhalation anaesthetic agent in clinical practice, is considered the cornerstone of this drug class because of its favourable characteristics, including smooth induction of anaesthesia, rapid post-operative recovery and minimal impact on hemodynamics. Several studies have demonstrated that SpostC can protect healthy myocardium from I/R injury, [6][7][8][9]28 but the underlying mechanism remains unclear. Interestingly, our previous studies found that the protective effects of SpostC on isolated myocardial mitochondria can be attributed to the upregulation of HIF-1a.…”
Section: Discussionmentioning
confidence: 99%
“…5 Sevoflurane is an ideal inhaled anaesthetic agent that is widely used in peri-operative anaesthesia. [6][7][8][9] Unfortunately, diabetes abolishes the cardioprotective effects of SpostC, [10][11][12] and the underlying mechanism remains unclear. [6][7][8][9] Unfortunately, diabetes abolishes the cardioprotective effects of SpostC, [10][11][12] and the underlying mechanism remains unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Akt signaling pathway plays an important role in cardiac growth, contractile function, and coronary angiogenesis [3]. A previous study demonstrated that sevoflurane reduced DOX-induced rat cardiac injury [4]. Thus, sevoflurane improves DOX-induced cardiac injury perhaps by affecting Akt signaling pathway.…”
Section: Introductionmentioning
confidence: 99%